(untitled) (Latakia University Journal - Economic and Legal Sciences Series, 2014)
يهدف البحث إلى تحديد العوامل المؤثرة على ربحية المصارف التجارية, وترتيبها حسب أهميتها النسبية, والمقارنة بين المصارف التجارية العامة والخاصة بخصوص العوامل التي تؤثر في ربحيتها. اعتمد البحث المنهج الوصفي التّحليلي. وكان من أهم نتائج البحث: 1- تتأثر ربحية المصارف التجارية السورية بمجموعة من العوامل يمكن تصنيفها ضمن فئتين: عوامل داخلية, وعوامل خارجية. 2- تختلف العوامل المؤثرة على ربحية المصارف التجارية في أهميتها النسبية, وكان أكثر العوامل تأثيراً الظروف الاقتصادية والسياسية, وتوظيف الموارد, والتشريعات القانونية والضوابط المصرفية. بينما كان عمر المصرف وعدد موظفي المصرف أقل العوامل تأثيراً. 3- لا توجد فروق دالة إحصائياً بين المصارف التجارية العامة والخاصة في العوامل الداخلية والخارجية التي تؤثر على ربحيتها. The research aims to identify the factors affecting the profitability of commercial banks, arranged according to their relative importance, and the comparison between commercial banks, public and private about the factors that affect their profitability. The research descriptive analytical method. One of the most important results: 1 - affected the profitability of commercial banks Syrian combination of factors can be classified in two categories: internal factors and external factors. 2 - different factors affecting the profitability of commercial banks in the relative importance of, and the most influential factor was economic and political conditions, and employing resources, legislation and legal and banking controls. While the age of the bank and the number of bank employees less influential factor. 3 - There are no statistically significant differences between commercial banks, public and private in the internal and external factors that affect their profitability.